Pattern and variations of the posterior interosseous artery of forearms in human adults - Thidar, Aye Mya; Shwe, Nilar; Aung, Htar Htar (2011)
Variations in the arterial pattern of the upper limb have been observed frequently, either in routine dissections or in clinical practice. Understanding of the vascular patterns of forearm and hand is necessary for microsurgical techniques in reconstruction of hand and upper extremity. To identify the variations of the posterior interosseous artery of forearm including the anastomosis patterns. Total 100 forearms were dissected. Data analysis was carried out by using SPSS for windows standard version release 11.5 statistical software. Posterior interosseous artery (PIA) originated from the common interosseous artery (78%) and ulnar artery (22%). The distal end of PIA anastomosed with the posterior branch of anterior interosseous artery in the form of an arch at dorsal side of the wrist 1.9-2.2 cm above the head of ulna. On both sides, the anastomotic arch terminated by giving branch only to the ulnar head (14%), only to the dorsal carpal arch (38%) ,to the unlar head and dorsal carpal arch (45%), to the ulnar head, dorsal carpal arch and radius (1%)respectively. The branch to dorsal carpal arch passed through fifth extensor compartment of the hand. Absence of anastomosis between anterior and posterior interosseous arteries was 2%. This study confirms that the anastomosis between interosseous arteries regarded as an important and significant anatomical feature both academically and clinically. The various anastomotic patterns of posterior interosseous artery are of great help clinically for applying the interosseous skin flaps in plastic and reconstructive surgery of the hand.